Improving the Effectiveness of Individual ABA Therapy of Autistic Children Through Addition Foldable Table Top - Purnamasari, Dwi Candra; Sari, Sinta M; Purwaningrum, Lu’lu’ (International Journal of Science and Applied Science: Conference Series, 2020)
Children with autism tend to have difficulty to sit still during therapy. This causes hindranceinthe therapy process. Applied Behavioral Analysis (ABA) is one of the best proven ways to treat children with autism. ABA method usually uses a special table called ABA table. However, the ABA table still has some problems in its use. When autistic children throw a tantrum, they often push the therapy table. This makes the therapists have to hold the table with their feet and hurts the therapists feet makes therapy ineffective. This study aims to investigate the effect of oval curvature,base mat addition and alternative designs of a foldable table top addition on the ABA table. The results of this evaluation are expected to improve the effectiveness of ABA table as a therapeutic tool. Research method used observations were carried out using three types of tables. Namely Table A, which is commonly used in ABA therapy, with oval curvatureon its edge and without a permanent base mat, and Table B, which is a table without oval curvature on its edge but with a permanent base mat and table C is equipped with a foldable table top and permanent base mat. Observationswere carried out on therapy sessions of 15 children with autism (12 boys, 3 girls) The results of the second stage testing show that table Cis the best recommendation for use in ABA therapy because it can help increase attention, overcome aggressive behavior and help trainself-developmentin children with autism.